2016
DOI: 10.3329/ajmbr.v1i3.26453
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of common parasitic and infectious diseases of goat at Babugonj upazilla, Barisal, Bangladesh

Abstract: This study was conducted to investigate the prevalence of common parasitic and infectious diseases of goat at Babugonj upazilla, Barisal, Bangladesh. The study was performed in Veterinary Clinic, ANSVM, PSTU and Upazilla Veterinary Hospital, Babugonj, Barisal during June, 2014 to May, 2015. The diseases were diagnosed on basis of clinical signs, owner’s statement, general clinical examinations and laboratory diagnosis. A socio-economic survey of 200 destitute women and marginal/poor farmers of Barisal district… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 16 publications
1
4
0
Order By: Relevance
“…Males (100%) were dominant in commercial farming system but in traditional farming system females (63.75%) were higher participants. The present finding was in agreement with work of Amin (2015). Less educated persons were involved in traditional goat farming system but higher number of commercial farmers were higher educated.…”
Section: Bibliography Of Traditional and Commercial Goat Rearing Farmerssupporting
confidence: 91%
“…Males (100%) were dominant in commercial farming system but in traditional farming system females (63.75%) were higher participants. The present finding was in agreement with work of Amin (2015). Less educated persons were involved in traditional goat farming system but higher number of commercial farmers were higher educated.…”
Section: Bibliography Of Traditional and Commercial Goat Rearing Farmerssupporting
confidence: 91%
“…The list of excluded articles together with the causes for their exclusion is provided in Appendix , Texts S2. A total of 196 eligible articles were used for systemic review and meta‐analysis (Abdalla, Majok, El Malik, & Ali, 2012; Abraham et al., 2005; Abubakar, Ali, & Khan, 2008; Abubakar, Jamal, Arshed, Hussain, & Ali, 2009; Abubakar, Jamal, Hussain, & Ali, 2008; Abubakar, Jamal, Khan, & Ali, 2008; Abubakar, Javed Arshed, Hussain, & Ali, 2011; Abubakar, Manzoor, et al, 2016; Abubakar, Rasool, et al, 2016; Abubakar, Zahur, Afzal, Ali, & Gonzales, 2017; Abubakar, Zahur, Naeem, Khan, & Qureshi, 2018; Acharya, Poudel, & Acharya, 2018; Adel, Abu‐Elzein, Al‐Naeem, & Amin, 2004; Adombi et al., 2017; Afera, Hussien, & Amsalu, 2014; Ahmad, Jamal, Ali, & Hussain, 2005; Ahmed et al., 2017; Ahmed, Rahman, Alam, Paul, & Uddin, 2016; Alam et al., 2018; Albayrak & Alkan, 2009; Albayrak & Gür, 2010; Al‐Dubaib, 2008, 2009; Ali, Intisar, & Khalafalla, 2014; Al‐Majali, Hussain, Amarin, & Majok, 2008; Almeshay et al., 2017; Ameen & Ajayi, 2013; Amin, 2015; Anees et al., 2013; Atta‐ur‐Rahman, Rahman, Akhtar, & Ullah, 2004; Ayim‐Akonor, Obese, Arthur, Owusu‐Ntumy, & Otsyina, 2014; Aytekin, Mamak, Ulucan, & Kalınbacak, 2011; Baazizi, Ait‐Oudhia, Parida, Mahapatra, & Khelef, 2015; Baazizi, Khelef, & Hussain, 2017; Balamurugan, Das, et al, 2014; Balamurugan, Krishnamoorthy, et al, 2014; Balamurugan et al., 2011; Balamurugan, Saravanan, et al, 2012; Banik, Podder, Samad, & Islam, 2008; Bari et al., 2018; Begum et al., 2016, 2017; Bello et al., 2016, 2018; Bhanuprakash et al., 2008; Bhaskar, Deshmukh, Chopade, Rautmare, & Aziz, 2011; Birindwa, George, Ntagereka, Christopher, & Lilly,...…”
Section: Resultsmentioning
confidence: 99%
“…Seasonsal incidence among Black Bengal goats was 22.86%, 14.61% and 12.17%in summer, rainy and winter season (Table 3 and Figure 3) and in Jamunapari goats highest incidence was 4.2% in summer season and 2.80% in winter season and no incidence occurred in rainy season (Table 4 and Figure 4). Amin (2015) showed that in summer season pneumonia was 6.72%, in rainy season 7.61% and in winter 12.56% respectively. Regarding the age, in case of Black Bengal goats the highest incidence (58.03%) was determined in kids followed by growing (30.19%) and adults (12.94%) (Table 5 and Figure 5).…”
Section: Pneumoniamentioning
confidence: 96%
“…In case of seasons, the highest incidence of contagious ecthyma in Black Bengal goats was found in winter season (1.21%) followed by summer season (0.81%) and rainy season (0.40%) (Table 3 and Figure 3) whereas the highest incidence of Jamunapari goats was found in summer season (0.35%) followed by rainy season (0.35%) and summer season (0%) (Table 4 and Figure 4). Mohammad Rohul Amin, 2015 showed that in summer season contagious ecthyma was 1.94%, in rainy season 1.22% and in winter 2.06% respectively. According to age, in case of Black Bengal goats the highest incidence was determined in growing goats (2.17%) followed by kid 2.08% and adult 0.55% (Table 5 and Figure 5).…”
Section: Contagious Ecthymamentioning
confidence: 99%